Game movement demands and physical profiles of junior, senior and elite male and female rugby sevens players - Clarke, A. C.; Anson, J. M.; Pyne, D. B. (Journal of Sports Sciences, 2017)
To inform recruitment, selection, training and testing of male and female rugby sevens players game running movement patterns and physical characteristics were quantified across junior, senior, and elite playing levels. Anthropometric and physical testing (40 m sprint, vertical jump, Yo-Yo IR1) occurred prior to players` national championships or international tournaments (n = 110 players), while game movements were obtained via GPS (n = 499 game files). The game movements of male players were similar across playing levels except for number of impacts >10 g which were 2 to 4-fold higher in elite (25.0 ± 11.2 impacts · game-1; mean ± SD), than junior (6.3 ± 3.5) and senior (11.8 ± 6.6) players. In men, there were fewer substantial correlations between on- and off-field measures which may reflect similar physical attributes across playing levels, and that other (strength, technical or tactical) factors may better differentiate these players. In females, elite players had more favourable on- and off-field performance measures than juniors and seniors, with moderate to strong correlations between on- and off-field variables. Female players should benefit from additional fitness training, while male players need to balance fitness with other technical and tactical factors.